Test and direct strength method on slotted perforated cold-formed steel channels subjected to eccentric compression. (15th June 2023) - Zhao, Jinyou; He, Jiaqi; Chen, Boshan; Zhang, Wenying; Yu, Shaole
Highlights: Tests on the behaviors of slotted perforated cold-formed steel (CFS) channels subjected to eccentric compression. A nonlinear elasto-plastic FE model was developed and validated against the experimental results. The extensive FE analyses were carried out for predicting the eccentricity impact coefficient formulas. The simplified DSM formulas of slotted perforated CFS channels subjected to eccentric compression were proposed, without the need to calculate the elastic buckling critical stress for slotted perforated CFS channels. Abstract: This paper aims to investigate the buckling behaviors of cold-formed steel (CFS) channels with slotted web holes determined by the Steel Stud Manufacturers Association (SSMA) under eccentric compression, and propose the simplified direct strength method (DSM) formulas for engineering practicing. An experimental study on 20 specimens was conducted, including 18 slotted perforated specimens with nine eccentricities increasing from −20 mm to 20 mm and 2 unperforated specimens subjected to axial compression. Two kinds of nominal lip lengths for cross sections were selected as 15 mm and 20 mm. The experimental results indicated that the failure modes of slotted perforated specimens subjected to eccentric compression depended on the position of the eccentricity. Compared with the slotted perforated specimens subjected to pure axial compression, the ultimate loads of specimens subjected to positive eccentric compression decreased by 21.70 % on average, while they decreased by 16.38 % on average for those subjected to negative eccentric compression. Moreover, a nonlinear elasto-plastic finite element model (FEM) was developed and validated against the experimental results. Furthermore, combined with the experimental results, extensive FE parametric analyses were conducted to predict the eccentricity impact coefficient formulas. Finally, based on DSM of unperforated CFS members subjected to pure axial compression in AISI S100-16 and the eccentricity impact coefficient formulas, the suitable DSM design formulas for slotted perforated CFS channels determined by the SSMA under eccentric compression were proposed, without the need to calculate the elastic buckling critical stress for slotted perforated CFS channels.